The Influence of Singing Activities on Children's Language Ability in the Pembina Siak Kecil State Kindergarten - Sari, Arfinda; Sefriany, Ririn; Mufaro’ah, Mufaro’ah (CV. Rayyan Dwi Bharata, 2024)
Singing activities at the Pembina Siak Kecil State Kindergarten are an effective learning method in improving the language skills of young children. Through various song lyrics, children not only introduce new vocabulary, but also learn to construct simple sentences. With pleasant melodies and themes that are relevant to everyday life, singing activities facilitate children to remember new words more easily. In addition, this activity also supports the development of grammar and sentence structure, as well as encouraging social interaction among children, improving their communication and collaboration skills. With the support of teachers and parents, children feel more confident in language and are able to communicate better. Singing activities also stimulate children's cognitive abilities and improve motor skills through movements that are integrated with singing. Repetition of songs in class provides an opportunity for children to internalize new vocabulary effectively. Teachers play an important role in choosing songs that are appropriate to the child's developmental stage, so that each child can learn according to their level of ability. Overall, singing activities at the Pembina Siak Kecil State Kindergarten have a significant impact on children's language development, enrich vocabulary, and build a strong communication foundation for the future.